Ultra-small nanodot modified BiOI / TiO2 photocatalyst as well as preparation method and application thereof
By synthesizing ultra-small BiOI nanodots in situ by pre-fixing on the TiO2 surface, the problems of uneven growth and agglomeration of BiOI nanodots were solved, and efficient BiOI/TiO2 photocatalysts were prepared, achieving excellent degradation efficiency of organic dyes and catalyst stability.
Patent Information
- Application Number
- CN202510014252.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-15
AI Technical Summary
The prior art is difficult to accurately control the growth velocity and direction of BiOI nanodots, resulting in uneven particle sizes and prone to agglomeration when synthesizing ultra-small nanodots, affecting photocatalytic performance.
Ultrasmall BiOI nanodots were synthesized in situ on the surface of TiO2 by pre-fixation, and TiO2 substrates with rutile structures were prepared by solvent-thermal method, and BiI3 was fixed on the surface of TiO2 at a specific temperature and stirring speed, and then converted into BiOI nanodots to ensure that their size is 3-5nm and prevent agglomeration.
Ultra-small nanodot modified BiOI/TiO2 photocatalyst was successfully prepared, which significantly improved the degradation efficiency of organic dyes, maintained the stability and efficient performance of the catalyst, and maximized the material utilization.
Smart Images

Figure CN119819332A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalysts, and in particular relates to a BiOI / TiO2 photocatalyst modified with ultra-small nanodots, a preparation method and application thereof. Background Art
[0002] In traditional semiconductor-mediated photocatalytic heterostructures, two or more components with suitable energy band arrangements are usually physically or chemically combined to construct a carrier diffusion channel driven by potential difference. In this way, photogenerated excitons can be effectively separated by interfacial carrier diffusion, which significantly slows down the loss of reaction sites and significantly improves the catalytic performance. For surface reactions such as photocatalytic reactions, the design of reducing the size and increasing the specific surface area is one of the effective solutions to increase the reaction efficiency. The size of the photocatalyst has a direct impact on its photocatalytic performance, because a smaller particle size means a larger specific surface area and more active sites. In recent years, in order to ensure efficient carrier separation and shorten its transmission distance, one nanoscale semiconductor component is preferentially decorated onto another nano- or micron-sized component, and thus a variety of photocatalytic heterostructures with nano-decorations have been developed.
[0003] BiOI is a compound with a unique crystal structure, and its basic unit is a layered structure formed by alternating Bi-O layers and II layers. Specifically, each Bi atom forms a BiO block with four O atoms, while each I atom is located on both sides of the BiO layer, forming an I-BiO-I sandwich structure. This layered structure gives BiOI good photoelectric properties and chemical stability. As an efficient visible light photocatalyst, BiOI has a wide spectral response, efficient photogenerated electron-hole separation, excellent redox ability, good environmental friendliness and chemical stability. These characteristics make BiOI have broad application prospects in environmental governance, antibacterial and clean energy.
[0004] However, due to the special layered structure of BiOI, its crystal growth rate is very fast and has a clear directionality, which causes the crystal to tend to form flakes or sheet structures during the growth process. In 2014, Jun Hu and others from Fuzhou University synthesized BiOI of different morphologies by replacing different solvents using the hot solvent method. But whether it is 3D or 2D BiOI, its basic unit is flake-like, and the smallest dimension in its structure can only reach 67nm, and other dimensions are several microns or above. By 2023, Tianyu Wang and others synthesized a pn junction-based heterojunction photocatalyst by modifying BiOI nanosheets on the surface of UiO-66, reducing the size of BiOI to 50nm. However, there are few reports on ultra-small BiOI nanodots.
[0005] In addition, the synthesis of BiOI ultra-small nanodots (particle size below 5nm) faces the following difficulties:
[0006] First, BiOI has a special layered molecular structure, which enables it to have fast crystal growth characteristics, and it is difficult to accurately control its growth speed and direction during the synthesis process, resulting in uneven particle size.
[0007] Second, small changes in reaction conditions such as temperature, pH, and reactant concentrations can significantly affect the size of the nanodots.
[0008] In addition, the smaller the particle size, the higher its surface energy, and thus the easier it is to agglomerate, requiring special attention during the synthesis process.
[0009] Therefore, how to control the morphology (size and structure) of BiOI nanodots while ensuring their crystalline structure to retain and optimize their photocatalytic performance remains a problem that needs to be solved. Summary of the invention
[0010] The purpose of the present invention is to overcome the deficiencies of the prior art, provide a BiOI / TiO2 photocatalyst modified with ultra-small nanodots, and a preparation method and use thereof, and solve the problems in the above-mentioned background technology.
[0011] One of the technical solutions adopted by the present invention to solve the technical problem is: providing a method for preparing a BiOI / TiO2 photocatalyst modified with ultra-small nanodots, characterized in that it comprises the following steps:
[0012] 1) Preparation of substrate: Preparation of rutile TiO2 crystals by solvothermal method;
[0013] 2) Pre-fixed synthesis of BiOI nanodots: Dissolve BiI3 in ethanol and mix with TiO2 crystals, and continuously stir at room temperature to obtain a mixture; then continue to stir the mixture at 70-90°C at a speed of 450-600rpm until the ethanol is completely evaporated, so that BiI3 is fixed on the TiO2 surface to obtain a brown powder; add the obtained brown powder into 45-60mL deionized water, and keep stirring at 70-90°C for 4-6h to convert the BiI3 on the TiO2 surface into BiOI in situ; wash and dry the product to obtain a BiOI / TiO2 heterojunction catalyst modified with ultra-small BiOI nanodots.
[0014] In the present invention, 1) prepare the substrate: mix butyl titanate and concentrated hydrochloric acid, slowly add oleic acid, stir for 15 to 20 minutes, transfer the solution to a high-pressure reactor, perform hydrothermal reaction at 160 to 190°C for 3 to 5 hours, and cool naturally to room temperature; wash and dry the obtained product, and calcine at 420 to 480°C for 0.8 to 1.2 hours to obtain TiO2 crystals with a rutile structure. Wherein, concentrated hydrochloric acid with a mass fraction of 35 to 37% is used, and the volume ratio of butyl titanate, concentrated hydrochloric acid, and oleic acid is 4:1.6 to 2:20. The obtained product is washed alternately with deionized water and ethanol for at least 3 to 6 cycles, and the obtained precipitate is dried in an oven at 80°C for 11 to 13 hours. The heating rate during the TiO2 calcination process is 0.5 to 10°C / min, and after being kept at 420 to 480°C for 1 hour, the muffle furnace door is kept closed and the temperature is naturally lowered to obtain TiO2 crystals with a rutile structure.
[0015] In step 2) of the present invention, 0.5-4 mg of BiI3 is dissolved in every 10 mL of ethanol and 100 mg of TiO2 crystals are added; preferably, 2 mg of BiI3 is dissolved in every 10 mL of ethanol and 100 mg of TiO2 crystals are added.
[0016] The second technical solution adopted by the present invention to solve the technical problem is: to provide a BiOI / TiO2 photocatalyst modified with ultra-small nanodots, which is prepared by the above method.
[0017] The present invention discloses a BiOI / TiO2 photocatalyst modified with ultra-small nanodots, comprising a TiO2 crystal substrate and BiOI ultra-small nanodots; the TiO2 crystal is a micron ball formed by self-assembly of nanorods; the BiOI ultra-small nanodots are lamellar crystals with a size of 3-5 nm, and are evenly distributed on the surface of the TiO2 crystal in a single layer without overlap. The diameter of the nanorods is 100-200 nm, and the diameter of the micron ball is 0.8-1.2 μm.
[0018] The third technical solution adopted by the present invention to solve its technical problem is: providing the use of the above-mentioned ultra-small nano-dot modified BiOI / TiO2 photocatalyst as a catalyst for degrading organic pollutants in water.
[0019] Compared with the background technology, this technical solution has the following advantages:
[0020] 1. The present invention combines the excellent photocatalytic activity of BiOI's unique flaky structure and substructure with the excellent electron transmission ability brought by the special built-in electric field structure of the pn junction, and synthesizes ultra-small BiOI nanodots (<5nm) on the TiO2 surface by pre-fixation. The obtained BiOI / TiO2 photocatalyst exhibits excellent degradation efficiency for organic dyes in water.
[0021] 2. The present invention retains the lamellar crystal structure of BiOI while successfully reducing its size to below 5nm. The pre-fixation method effectively prevents agglomeration. BiOI nanodots are distributed in a single layer on TiO2 without agglomeration or overlap, which maximizes the material utilization rate. The smaller size means a larger specific surface area and more reaction sites, which is beneficial to surface reactions such as catalytic degradation.
[0022] 3. The BiOI / TiO2 photocatalyst prepared by the present invention exhibits excellent degradation performance for organic dyes under different light sources. And through characterization analysis of the catalyst before and after the reaction, it was found that the heterojunction showed excellent stability during the catalytic process, and the crystal shape and morphology did not change significantly. The cycle test found that after 4 cycles, the catalyst still maintained 80% of the original degradation effect. In addition, through the comparison of total organic carbon before and after the reaction, it was found that after about 2 hours of illumination, the organic dye was completely mineralized. Therefore, the catalyst can be used for the green, rapid and efficient removal of organic matter in water bodies;
[0023] 4. Based on the special heterojunction structure of the present invention, the self-quenching effect of the reaction sites existing in the heterojunction catalyst is proposed, which further improves the theoretical research on electron transport in the heterojunction catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The XRD spectra of the photocatalysts prepared in Examples 1-4.
[0025] Figure 2 HRTEM images of the photocatalysts prepared in Examples 1-4.
[0026] Figure 3 The photocatalysts prepared in Examples 1-4 show the degradation effects on organic dyes under different light sources.
[0027] Figure 4 The degradation performance test results of the photocatalysts prepared in Examples 1-4, including the cyclic test results of organic dye degradation under simulated sunlight (left) and the XRD spectra before and after the degradation of the organic dye (right).
[0028] Figure 5The fluorescence lifetime curves (left) and fitting results (middle and right) of the photocatalysts prepared in Examples 1-4. DETAILED DESCRIPTION
[0029] In the following examples, the prepared ultra-small nanodot-modified BiOI / TiO2 heterojunction photocatalyst is named TiO2@BiOI-X, where X represents the weight ratio of BiI3 and TiO2 used in the reaction, and X=0.5, 1, 2 and 4 respectively represent that in each synthesis, the amount of TiO2 used is 100 mg, and the amount of BiI3 used is 0.5 mg, 1 mg, 2 mg and 4 mg respectively. The room temperature in the examples refers to 23-26°C.
[0030] Examples 1-4
[0031] The method for preparing the ultra-small nano-dot modified BiOI / TiO2 photocatalyst in the embodiment comprises the following steps:
[0032] 1) Preparation of substrate: A rutile phase TiO2 substrate was prepared using a solvothermal method.
[0033] 4mL of butyl titanate and 1.85mL of concentrated hydrochloric acid (mass fraction of 37%) were mixed evenly, then slowly added to 20mL of oleic acid, mixed evenly under magnetic stirring, poured into a hydrothermal kettle, reacted at 180°C for 4 hours, the obtained product was naturally cooled to room temperature, and washed alternately with deionized water and ethanol for at least 3 cycles, the obtained precipitate was dried in an oven at 80°C for 12 hours, and then heated at a rate of 1°C / min in a muffle furnace, and the obtained precipitate was kept calcined at 450°C for 1 hour, without opening the muffle furnace door, and cooled naturally, and the final product was a TiO2 crystal support material. The obtained TiO2 crystal support material is a pure rutile phase, and its morphology is a micron sphere formed by self-assembly of nanorods (diameter of about 150nm), and the sphere diameter is about 1mm.
[0034] 2) Pre-fixation of synthesized BiOI nanodots:
[0035] After mixing different amounts of BiI3 (0.5mg, 1mg, 2mg, 4mg) with 10mL ethanol, 100mg of the prepared TiO2 crystals were added and stirred for 2h at room temperature to mix evenly. The mixture was then placed on a stirring table at 80°C and stirred at 500rpm until the ethanol evaporated completely. The obtained brown powder was added to 50mL deionized water and stirred at 90-100°C for 4-6h. The product was washed with ethanol and deionized water for 3-6 times in sequence, and then dried at 60-100°C for 5-6h. The obtained products were marked as BiOI / TiO2-0.5, BiOI / TiO2-1, BiOI / TiO2-2, and BiOI / TiO2-4.
[0036] 1. Material Characterization:
[0037] The BiOI / TiO2 photocatalysts prepared in the above examples 1-4 were subjected to X-ray diffraction scanning ( Figure 1 ) found that the peak of BiOI was observed in the BiOI / TiO2-4 sample, indicating that BiOI crystals were successfully prepared. In addition, the obtained BiOI / TiO2-4 photocatalyst has the characteristic peaks of both TiO2 and BiOI, proving that the crystal shape of BiOI has been completely preserved.
[0038] High-resolution transmission electron microscopy (HRTEM) observations revealed that Figure 2 ), BiOI presents the morphology of nanodots, with a size of 3-5nm, and is evenly distributed on the TiO2 surface. As the amount of BiI3 increases, the number of BiOI nanodots generated also increases. At the same time, even in the BiOI / TiO2-4 sample with the highest content, no agglomeration or overlap occurs, proving that the method of pre-fixing the reactants can be used as an effective method to synthesize ultra-small nanodots on the crystal surface.
[0039] 2. Performance Analysis:
[0040] 1. Analysis of photocatalytic activity effect:
[0041] Rhodamine B was used as an organic indicator to further verify the catalytic degradation of organic pollutants by the synthesized photocatalytic heterojunction ( Figure 3 The results showed that the increase in BiOI content helped to improve the catalytic degradation efficiency of RhB and broaden the catalyst's response range to light. The heterojunction showed better degradation effects than when the two existed alone under all light sources (including visible light, ultraviolet light, and simulated sunlight). Among them, BiOI / TiO2-2 had the best catalytic effect.
[0042] 2. Material stability analysis:
[0043] Taking BiOI / TiO2-2 as an example, a cyclic experimental study on the catalytic degradation of RhB was conducted. The results showed that after four cyclic tests, the obtained catalyst still retained nearly 80% ( Figure 4 Left), and from the XRD spectra of the heterojunction photocatalyst before and after participating in the degradation of organic dyes, it can be seen that ( Figure 4 Right), the crystal shape of BiOI hardly changes before and after the reaction, indicating that the catalyst has stable chemical properties and practical use value.
[0044] 3. Study on the mechanism of photocatalytic reaction:
[0045] The photogenerated charge lifetime and behavior test was performed as follows: 10 mg of powder was placed on an optical platform, irradiated with incident light at 420 nm, and its fluorescence decay was recorded at 550 nm. Figure 5 .
[0046] The spectrum fitting analysis found that ( Figure 5 ), there are two charge recombination processes in the heterojunction. The recombination inside BiOI is not affected by the heterojunction, so its fluorescence lifetime remains basically unchanged, while the fluorescence lifetime at the heterojunction interface decreases with the increase of BiOI. Therefore, although the formation of the heterojunction will promote charge separation and improve the efficiency of the generated charge utilization, the excess will instead bring about a large amount of interface recombination, resulting in a decrease in efficiency.
[0047] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a BiOI / TiO2 photocatalyst modified with ultra-small nanodots, characterized in that: The steps include: 1) Preparation of substrate: Preparation of rutile TiO2 crystals by solvothermal method; 2) Pre-fixed synthesis of BiOI nanodots: Dissolve BiI3 in ethanol and mix with TiO2 crystals, and continuously stir at room temperature to obtain a mixture; then continue to stir the mixture at 70-90°C at a speed of 400-600 rpm until the ethanol evaporates completely, so that BiI3 is fixed on the TiO2 surface to obtain a brown powder; add the obtained brown powder into deionized water, and continue to stir at 70-90°C for 4-6 hours to convert the BiI3 on the TiO2 surface into BiOI in situ; wash the product with deionized water, and dry it at 80-100°C for 5-6 hours to obtain a BiOI / TiO2 heterojunction catalyst modified with ultra-small BiOI nanodots.
2. The method for preparing a BiOI / TiO2 photocatalyst modified with ultra-small nanodots according to claim 1, characterized in that: 1) Preparation of substrate: Mix butyl titanate and concentrated hydrochloric acid, slowly add into oleic acid, stir for 10 to 30 minutes, transfer the solution into a high pressure reactor, carry out hydrothermal reaction at 160 to 190° C. for 3 to 5 hours, and cool naturally to room temperature; wash and dry the obtained product, and calcine at 420 to 480° C. for 0.8 to 1.2 hours to obtain TiO2 crystals with rutile structure.
3. The method for preparing a BiOI / TiO2 photocatalyst modified with ultra-small nanodots according to claim 2, characterized in that: In step 1), concentrated hydrochloric acid with a mass fraction of 35-37% is used, and the volume ratio of butyl titanate, concentrated hydrochloric acid and oleic acid is 4:1.6-2:
20.
4. The method for preparing a BiOI / TiO2 photocatalyst modified with ultra-small nanodots according to claim 2, characterized in that: In step 1), the obtained product is washed alternately with deionized water and ethanol for 3 to 6 cycles, and the obtained precipitate is dried in an oven at 60 to 100° C. for 11 to 13 hours.
5. The method for preparing a BiOI / TiO2 photocatalyst modified with ultra-small nanodots according to claim 2, characterized in that: In step 1), the heating rate during the TiO2 calcination process is 0.5-10°C / min, and after maintaining at 420-480°C for 0.8-1.2h, the muffle furnace door is kept closed and the temperature is naturally lowered to obtain TiO2 crystals with a rutile structure.
6. The method for preparing a BiOI / TiO2 photocatalyst modified with ultra-small nanodots according to claim 1, characterized in that: In step 2), 0.5-4 mg of BiI3 is dissolved in every 10 mL of ethanol and 100 mg of TiO2 crystals is added.
7. An ultra-small nanodot-modified BiOI / TiO2 photocatalyst, characterized in that: The method is prepared by the method according to any one of claims 1 to 6.
8. An ultra-small nanodot-modified BiOI / TiO2 photocatalyst, characterized in that: It includes a TiO2 crystal substrate and BiOI ultra-small nanodots; the TiO2 crystals are micron balls formed by self-assembly of nanorods; the BiOI ultra-small nanodots are lamellar crystals with a size of 3-5nm, and are evenly distributed on the surface of the TiO2 crystal in a single layer without overlap.
9. The ultra-small nanodot-modified BiOI / TiO2 photocatalyst according to claim 8, characterized in that: The diameter of the nanorod is 100-200 nm, and the diameter of the microsphere is 0.8-1.2 μm.
10. The use of the ultra-small nanodot-modified BiOI / TiO2 photocatalyst as claimed in claim 8, characterized in that: Catalysts for the degradation of organic pollutants in water.